Molecular Identification of Isolate from Escherichia coli Isolates from Dialysis Patients - Husham Hachim Mohammed; Mohammed Flayyih Tareef; Ali Kamal Mohammed (Journal of Pure and Applied Microbiology, 2018)
The aim of this present study to was to detect the 16S rRNA gene sequences of Escherichia coli local isolate from dialysis patients and to compare their genetic relatedness utilizing phylogenetic analysis. A total of (75) clinical samples (Urine) were collected from in dialysis patients but found thirty specimens of E. coli admitted at Baghdad Medical City, Baghdad Teaching Hospital during the period from October, 2017 to January, 2018 platinum calibrated sterile wire loop to transfer 1µl of the uncentrifuged urine specimen and streaked on MacConkey agar incubated at 37°C for 18-24 hours. The results of phylogenetic analysis showed that Proximity and the genetic dimension among themselves and the world with more than 98% to 99%compatibility values.